Use of analgesics in the general population: Trends, persistence, high-risk use and associations with pain sensitivity - Samuelsen, Per-Jostein (UiT The Arctic University of Norway, 2016)
Paper II and III of this thesis are not available in Munin Paper II: Samuelsen, P. J., Svendsen, K., Wilsgaard, T., Stubhaug, A., Nielsen, C. S., Eggen, A.E.: “Persistent analgesic use and the association with chronic pain and other risk factors in the population - a longitudinal study from the Tromsø Study and the Norwegian Prescription Database”. Available in European Journal of Clinical Pharmacology 2016 Paper III: Samuelsen, P. J., Nielsen, C. S., Wilsgaard, T., Stubhaug, A., Svendsen, K., Eggen, A. E.: “Pain sensitivity as risk factor for analgesic use in 10,486 adults: The Tromsø Study”. (Manuscript) Background: Analgesics are commonly used drugs but we are lacking knowledge of trends, persistence, high-risk use and the association with pain sensitivity at a population-level. Purpose: To describe the use of analgesics, particularly persistent analgesic use, in a general population (30+ years), including change over time, contraindications and drug interactions, risk factors, and associations with pain sensitivity. Methods: The Tromsø Study, including Tromsø 5 (2001-02, n = 8,030) and Tromsø 6 (2007-08, n = 12, 981), with the latter further linked with the Norwegian Prescription Database (2004-13). Main results: The age-adjusted prevalence of analgesic use increased from 53.7% to 59.6% in women and from 29.1% to 36.7% in men between 2001 and 2008, due to an increase in the use of non-prescription analgesics. Several areas of potential high-risk use of analgesics were identified. The prevalence of persistent prescription analgesic use was 4.3% in general and 10.2% among those reporting chronic pain, while the incidence rate was 21.2 per 1,000 person-years; risk factors were chronic pain, increasing age, female sex, lower education level and most likely lower levels of physical activity. Analgesic use was associated with increased pain sensitivity; regular opioid users were more pain sensitive than regular users of non-opioid analgesics. Increased pain sensitivity was a risk factor for future persistent ...